Smoothed particle hydrodynamics numerical model for modeling an oscillating water chamber. (1st September 2016) - Didier, Eric; Neves, Diogo R.C.B.; Teixeira, Paulo R.F.; Dias, João; Neves, Maria Graça
Abstract: This paper presents the application and the validation of the SPH numerical model SPHyCE, based on a standard Smoothed Particle Hydrodynamics formulation, for modeling an onshore oscillating water chamber, comparing results of amplification factor and phase lag with those obtained by a mesh-based RANS model. Firstly, an analysis of the results for different resolutions (i.e. particle dimension) showed the independence of results with refinement. Secondly, the amplification factor of mean free surface elevation inside the oscillating water chamber and the phase lag between time series of free surface elevation outside and inside the water chamber were analysed. A good agreement was achieved between the mesh free SPHyCE model and the mesh-based RANS model. SPHyCE model was finally applied to analyse the hydrodynamic fluid flow inside and outside the water chamber and to quantify the forces on the vertical wall and the amplification factor for different incident wave heights for a rough sea state with complex wave breaking, impact loads and overtopping, contributing to the future applications of SPH models for development and studies of OWC devices. Highlights: Numerical modeling of oscillating water column using a SPH numerical model. Convergence study with resolution are presented. Validation of SPH model by comparing results with mesh-based RANS numerical model. Application of SPH model for a rough sea state with wave breaking and impact loads. Forces and amplification factor are calculated for different incident wave heights.